Penggunaan Protein Membran Stadium Bradizoit Toxoplasma gondii untuk Mendiagnosis Toksoplasmosis dengan Metode Intradermal Test - Hanafiah, Muhammad; Nurcahyo, Wisnu; Aliza, Dwinna; Karmil, Teuku Fadrial (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
A research was conducted to find out an alternative diagnose in detecting toxoplasmosis in livestock/animal using intradermal test  from protein membrane of  T. gondii bradizoite stage. Local isolate ofmembrane T. gondii bradizoite stage  was used in the research. Ten of domestic sheep with the age of ± 1year and 10 mice strain Balb/c with the age ± 2 month were used in this research. The reaction ofhypersensitivity on the skin post protein membrane bradyzoite injection was indicated by the process ofskin thickening. The diameter skin thickening was measured using cutimeter, in which diameter e” 10 mmindicated positive diagnose. The result showed that optimal dosage of membran protein bradyzoite thatcould be applied to detect toxoplasmosis in livestock and animal using intradermal test were 0,6 ml and0,2 ml for sheep and mice respectively. The sensitivity and specificity level of antigen use (protein membrane)of T. gondii bradizoite stage from local isolate to diagnose toxoplasmosis in mice using intradermal testwere: 85.0 %  and 66.6 % respectively, while in sheep the sensitivity and specificity level were 85.0 % and66.6 % respectively. It can be concluded that  intradermal  test was appropriate to be implemented fordetecting toxoplasmosis in sheep and mice induced with tachyzoite T. gondii.
Keywords: isolation, bradyzoite, material diagnose, T. gondii